Prevalence and Associated Factors of Depression, Anxiety and Insomnia Symptoms Among Patients Receiving Ophthalmic Consultation Online During the COVID-2019 Pandemic - Ding, Lin; Guo, Ni; Zhu, Jianing; Tuxunjiang, Dilinuer; Abudoukeremuahong, Aierxiding; Zuo, Chengguo; Lin, Mingkai (Frontiers in Psychiatry, 2022)
Objective This study aims to assess the prevalence and associated factors of depression, anxiety and insomnia symptoms among patients undergoing ophthalmic consultation online during the coronavirus disease 2019 (COVID-2019) pandemic. Methods We reviewed the data of patients who received online ophthalmic consultations during the lockdown period from February to August 2020, and an online survey was conducted among them. We collected the respondents' demographic data and their attitudes toward the online consultation, assessed the depression, anxiety and insomnia symptoms and estimated associated factors by logistic regression analysis. Results The online service provided 425 consultations during the COVID-19 lockdown period. Of these eligible subjects, 139 patients responded to an invitation to participant in the study (105/75.5% were females, and 40/28.8% were health care workers). More than half of the participants reported that they trusted and were satisfied with the online consultation (109/78.4% and 82/59%, respectively). Fifty-two (37.4%), 32 (23.0%), and 53 (38.1%) patients showed symptoms of depression, anxiety, and insomnia, respectively. Depression was found to be significantly more common in health care workers (P = 0.019) and those who were basically satisfied with online consultation (P = 0.024). Anxiety was more common among participants who had used electronics for a long time (P = 0.038). Binary logistic regression showed health care work as a risk factor for depressive symptoms (odds ratio [OR]: 2.424; 95% CI: 1.143–5.143; P = 0.021). Conclusion Psychological distress is highly prevalent among patients who were involved in online consultation for ocular manifestations during the COVID-19 lockdown period. In the context of a major public health event, ophthalmologists should focus not only on ocular symptoms but also on the mental health of their patients, and appropriate psychological support should be given.